Grain iron and zinc content is independent of anthocyanin accumulation in pigmented rice genotypes of Northeast region of India - Gogoi, Smrita; Singh, Sanjay; Swamy, B.P. Mallikarjuna; Das, Priyanka; Sarma, Debojit; Sarma, Ramendra Nath; Acharjee, Sumita; Deka, Sharmila Dutta (Springer, 2024)
The traditional rice genotypes of Assam are considered to have biological value due to the presence of several bioactive compounds like flavonoids, polyphenols, and anthocyanins, which have antioxidant, anti-cancer, anti-diabetic, and anti-aging properties. The pigmented genotypes are considered to have high iron (Fe) content. However, the effect of Fe and Zinc (Zn) accumulation on anthocyanin content is yet to be studied in pigmented rice of Assam. We studied the Fe, Zn, and anthocyanin content in grains of 204 traditional rice of Assam, which are traditionally preferred for their nutraceutical properties. We performed phenotypic and biochemical compositional analyses of 204 genotypes to identify those having high Fe, Zn, and anthocyanin. We also carried out the differential expression of a few selected Fe and Zn transporter genes along with the expression of anthocyanin biosynthesis genes. Interestingly, all pigmented rice genotypes contained a higher amount of phenolic compound than the non-pigmented form of rice. We found the highest (32.73 g) seed yield per plant for genotype Jengoni followed by Kajoli chokuwa and Khau Pakhi 1. We also listed 30 genotypes having high levels of Fe and Zn content. The genotype Jengoni accumulated the highest (186.9 μg g−1) Fe, while the highest Zn (119.9 μg g−1) content was measured in genotype Bora (Nagaon), The levels of Ferritin 2 gene expression were found to be significantly higher in Bora (Nagaon) (> 2-fold). For Zn accumulation, the genotype DRR Dhan-45, which was released as a high Zn content variety, showed significant up-regulation of the ZIP4 gene at booting (> 7-fold), post-anthesis (7.8-fold) and grain filling (> 5-fold) stages followed by Bora (Nagaon) (> 3-fold) at post-anthesis. Anthocyanidin synthase gene, Flavanone 3-dioxygenase 1-like (FDO1), and Chalcone-flavanone isomerase-like genes were up-regulated in highly pigmented genotype Bora (Nagaon) followed by Jengoni. Based on our data there was no significant correlation between iron and zinc content on the accumulation of anthocyanin. This challenges the present perception of the higher nutritive value in terms of the micronutrient content of the colored rice of Assam. This is the first report on the detailed characterization of traditional rice genotypes inclusive of phenotypic, biochemical, nutritional, and molecular attributes, which would be useful for designing the breeding program to improve Fe, Zn, or anthocyanin content in rice.